(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Abstract The financial system has been revolutionized by recent advancements in banking and insurance, although only to a limited extent. This study investigates the current state of financial inclusion in Uttar Pradesh, as well as the government’s efforts toward financial literacy and awareness programs that were implemented. People with low earnings are unable to obtain traditional financial products such as bank accounts, credit, remittances and payment services, financial advising services,